Renin-Angiotensin System Genes Polymorphisms and Essential Hypertension in Burkina Faso, West Africa. (17th August 2015) - Tchelougou, Daméhan; Kologo, Jonas K.; Karou, Simplice D.; Yaméogo, Valentin N.; Bisseye, Cyrille; Djigma, Florencia W.; Ouermi, Djeneba; Compaoré, Tegwindé R.; Assih, Maléki; Pietra, Virginio; Zabsonré, Patrice; Simpore, Jacques
Abstract : Objective. This study aimed to investigate the association between three polymorphisms of renin-angiotensin system and the essential hypertension in the population of Burkina Faso. Methodology. This was a case-control study including 202 cases and 204 matched controls subjects. The polymorphisms were identified by a classical and a real-time PCR. Results. The AGT 235M/T and AT1R 1166A/C polymorphisms were not associated with the hypertension while the genotype frequencies of the ACE I/D polymorphism between patients and controls (DD: 66.83% and 35.78%, ID: 28.22% and 50.98%, II: 4.95% and 13.24%, resp.) were significantly different ( p < 10 −4 ). The genotype DD of ACE gene (OR = 3.40, p < 0.0001), the increasing age (OR = 3.83, p < 0.0001), obesity (OR = 4.84, p < 0.0001), dyslipidemia (OR = 3.43, p = 0.021), and alcohol intake (OR = 2.76, p < 0.0001) were identified as the independent risk factors for hypertension by multinomial logistic regression. Conclusion. The DD genotype of the ACE gene is involved in susceptibility to hypertension. Further investigations are needed to better monitor and provide individualized care for hypertensive patients.